Evaluation of dried fermented biomass as a feed ingredient in plant‐based practical diets for juvenile Pacific white shrimp Litopenaeus vannamei. (11th May 2017) - Qiu, X.; Davis, D.A.
Abstract: Two growth trials were designed to evaluate the utilization of dried fermented biomass (DFB) in commercial type feed formulation for Pacific white shrimp, Litopenaeus vannamei . In trial 1, four experimental diets were formulated to utilize increasing levels (0, 25, 50 and 100 g/kg) of spray‐dried fermented biomass (SDFB) as a replacement of fish meal (FM). Results indicated that SDFB can be utilized up to 50 g/kg as a substitution for FM without causing growth depression in shrimp. However, dietary SDFB supplementation at 100 g/kg significantly reduced the weight gain (WG) of shrimp and increased feed conversion ratio (FCR). This reduction in performance is likely due to palatability or nutrient imbalances of the feed. In trial 2, nine experimental diets were formulated with increasing levels (0, 20, 40, 60 and 120 g/kg) of spray‐dried (S) or granular (G) DFB to replace soy protein concentrate (SPC) or SPC + corn protein concentrate (CPC). This allowed the comparison between spray‐dried and ring‐dried products. Ring drying produced a granular product, reducing dust and increasing product particle size. Shrimp fed with diet containing 20 g/kg GDFB performed the best in terms of final mean weight, WG and FCR. Significantly reduced growth and increased FCR were observed in shrimp fed diets containing 60 and 120 g/kg SDFB. Lipid content of whole body was significantly reduced when GDFB was incorporated at 120 g/kg. No significant differences were detected in survival, protein retention efficiency as well as protein and ash contents of the whole shrimp. Results from analysis of covariance indicated that the processing method (covariant) had a significant effect on final mean weight, WG and FCR. In general, shrimp fed with diet containing granular product performed better as compared to those fed with diets utilizing spray‐dried product. GDFB can be utilized in the diets up to 120 g/kg in practical shrimp feeds as a substitute for SPC and CPC without compromising the growth of shrimp. However, a significant reduction in WG was observed in the diets containing 60 and 120 g/kg SDFB. The results in the current study demonstrate that processing changes to produce a granular product produced an improved feed ingredient for shrimp.